Some Properties of Oyster Mushroom Grown on Substrates Containing Paper Waste - Joko Sulistyo (Fakultas MIPA UNM, 2023)
ABSTRACTThis study was conducted to determine the activity of starter culture of oyster mushroom and influence of substrates containing paper waste materials used to grow the mushroom. The purpose of the study was to analyze nutritional value and antioxidant activity of the mushroom grown on the substrate contained paper waste. The substrate was prepared using paper waste with 5 different formulations were 0% (control), 20%, 30%, 40%and 50% paper waste. Proximate analysis, heavy metal content and antioxidant activity were carried out to test the quality of the mushroom. Overall, the mushroom grown on the substrates containing paper waste showed high water content, however, the mushroom grown on the substrate contained 50% paper waste showed the highest content of ash, protein, and crude fiber, while higher fat content showed by the mushroom grown on the substrate contained 50% paper waste compared to the mushroom grown on other substrate with different composition of paper waste. The mushroom grown on the substrate contained 50% paper waste indicated considerably high content of heavy metals such as lead, (3.5%), copper (20.8%) and cadmium (4.4%), respectively however, it showed the higher antioxidant activity (87.19%) as well compared to the mushrooms grown on the substrate containing a lower percentage of paper waste, thus giving a conclusion that there was probably positive correlation in between the heavy metals contained in paper waste with antioxidant activity. Keywords: paper waste, oyster mushroom, proximate analysis, antioxidant, heavy metals. ABSTRAKPenelitian ini dilakukan untuk menentukan aktivitas kultur starter jamur tiram dan menguji substrat yang mengandung limbah kertas yang digunakan untuk menumbuhkan jamur. Tujuan penelitian adalah untuk menganalisis nilai gizi dan aktivitas antioksidan dari jamur yang ditumbuhkan pada substrat mengandung limbah kertas. Substrat disiapkan menggunakan limbah kertas dengan 5 formula berbeda yaitu 0% (control), 20%, 30%, 40% dan 50%. Analisis proksimat, kandungan logam berat dan aktivitas antioksidan dilakukan untuk menguji kualitas dari jamur. Secara keseluruhan, jamur tiram yang ditumbuhkan pada substrat limbah kertas menunjukkan kadar air yang tinggi, namun jamur yang ditumbuhkan pada substrat mengandung 50% limbah kertas menunjukkan kadar abu, protein, dan serat kasar yang tertinggi, sementara kadar lemak pada jamur yang ditumbuhkan pada substrat mengandung 50% limbah kertas menunjukkan lebih tinggi dibandingkan dengan jamur yang ditumbuhkan pada substrat dengan komposisi limbah kertas lainnya. Jamur yang ditumbuhkan pada substrat mengandung 50% limbah kertas menunjukkan kandungan logam berat, masing-masing seperti timbal (3.5%), tembaga (20.8%) dan kadmium (4.4%) yang cukup tinggi, namun juga menunjukkan aktivitas antioksidan yang lebih tinggi (87.19%) dibandingkan dengan jamur yang ditumbuhkan pada substrat mengandung persentase limbah kertas yang lebih rendah, sehingga memberikan kesimpulan bahwa terdapat korelasi yang positif antara logam berat yang terkandung dalam limbah kertas dengan aktivitas antioksidan.Kata kunci: limbah kertas, jamur tiram, nilai gizi, analisis proksimat. Antioksidan, logam berat.